Palonosetron for the prevention of chemotherapy-induced nausea and vomiting in patients with cancer. (July 2010) - Navari, Rudolph M
Chemotherapy-induced nausea and vomiting (CINV) is associated with a significant deterioration in quality of life. The emetogenicity of the chemotherapeutic agents, repeated chemotherapy cycles and patient characteristics (e.g., female gender, younger age, low alcohol consumption and history of motion sickness) are the major risk factors for CINV. This article provides a detailed description of palonosetron, a second-generation 5-hydroxytryptamine-3 (5-HT3 ) receptor antagonist, which has been approved for the prevention of acute CINV in patients receiving either moderately or highly emetogenic chemotherapy and for the prevention of delayed CINV in patients receiving moderately emetogenic chemotherapy. In recent studies, compared with the first-generation 5-HT3 receptor antagonists, palonosetron in combination with dexamethasone demonstrated better control of delayed CINV in patients receiving highly emetogenic chemotherapy and had a similar safety profile. Owing to its efficacy in controlling both acute and delayed CINV, palonosetron may be very effective in the clinical setting of multiple-day chemotherapy and bone marrow transplantation.